The Principles of Pentahelix in Supporting the Awareness of State Defense in the Millennial Generation in the Globalization Era - Elizamiharti; Doly Andhika Putra (PT FORMOSA CENDEKIA GLOBAL, 2022)
One of the problems facing Indonesia today is the fading of nationalism and patriotism among the younger generation. The millennial generation, which is the backbone of the nation, must have an awareness of defending the country by remaining firm on Indonesia's cultural values. The purpose of this study was to see how far the development of the Penta helix model can support awareness of defending the country in the millennial generation. This study uses a descriptive qualitative research method using theoretical data from various kinds of literature. . The data is then analyzed inductively and closed and presented clearly with descriptive. Based on the results of the research, it can be concluded that the values of defending the country that has been initiated to increase awareness of defending the country for the millennial generation consist of Love for the Motherland, Awareness of the Nation and State, Confidence in Pancasila as the state ideology, Willingness to sacrifice for the Nation and State and Having initial abilities State Defense.